Lack of Authority, Failure of Leadership : Burden of Not Being Led - Reunanen, Tero; Eckhaus, Eyal (Springer, 2020)
The purpose of this research is to scrutinize the difference between autocratic leadership and absence of leadership. We utilized simple division between autocratic leader and laissez-faire leader in order to find out how these stereotypical leaders’ are affecting the followers. Typically, autocratic leadership is situated to be bad leadership approach and follower’s freedom is emphasized. Cognitive constructivism and empowerment of followers are embracing the freedom and followers own responsibility. However, the question for best approach for leadership is too complex to be answered with easy solutions. Real world cases rarely fit to ideal models. In this article, we analyze how these two types of extreme ends in leadership behavior affect the followers’ feeling of certainty. We show how these approaches affect to followers by analyzing open answers with a mix method design with both quantitative and qualitative analysis.
Keywords: leadership; Machine learning; management; NLP; Organizational behavior; Role; fi=Tuotantotalous|en=Industrial Management|